Genetic Stability and Fitness of Aedes aegypti Red-Eye Genetic Sexing Strains With Pakistani Genomic Background for Sterile Insect Technique Applications - Misbah-ul-Haq, Muhammad; Carvalho, Danilo O.; Duran De La Fuente, Lucia; Augustinos, Antonios A.; Bourtzis, Kostas (Frontiers in Bioengineering and Biotechnology, 2022)
The mosquito species Aedes aegypti is the primary transmitter of viruses that cause endemic diseases like dengue in Pakistan. It is also a cause of other vector-borne diseases like yellow fever, Zika fever, and chikungunya, which significantly impact human health worldwide. In the absence of efficient vaccines (except for yellow fever) or drugs, vector control methods, such as the sterile insect technique (SIT), have been proposed as additional tools for the management of these diseases. Mosquito SIT programs are based on the release of sterile males and it is important female releases to be ideally zero or to be kept at a minimum, since females are the ones that bite, blood-feed and transmit pathogens. Recently, an Ae. aegypti genetic sexing strain (GSS), with and without a recombination-suppressing inversion (Inv35), was developed using the eye color as a selectable marker, with males having black eyes and females red eyes. In the present study, we introgressed the sexing features and the Inv35 of the Ae. aegypti red-eye GSS into the Pakistani genomic background aiming to their future use for SIT applications in the country. Both introgressed strains, the Red-eye GSS-PAK and the Red-eye GSS/Inv35-PAK, were evaluated in respect to their genetic stability and biological quality by assessing parameters like recombination rate, fecundity, fertility, pupal and adult recovery, time of development, pupal weight, survival, and flight ability in comparison with a wild Pakistani population (PAK). The results suggest that the sexing features and the recombination suppression properties of Inv35 were not affected after their introgression into the local genomic background; however, some biological traits of the two newly constructed strains were affected, positively or negatively, suggesting that a thorough quality control analysis should be performed after the introgression of a GSS into a new genomic background prior to its use in SIT field trials or applications. The importance of using GSS with local genomic background for SIT applications against Aedes aegypti is also discussed.